1-Ethyl 3-methylimidazolium thiocyanate ionic liquid as corrosion inhibitor of API 5L X52 steel in H2SO4 and HCl media. (June 2019) - Corrales-Luna, Mónica; Le Manh, Tu; Romero-Romo, Mario; Palomar-Pardavé, Manuel; Arce-Estrada, Elsa M.
Highlights: 1-Ethyl 3-methylimidazolium thiocyanate is experimentally and theoretically evaluated as corrosion inhibitor in H2 SO4 and HCl solutions. Ethyl 3-methylimidazolium thiocyanate as inhibitor presents a better efficiency in H2 SO4 than that in HCl solution. The behavior of 1- ethyl 3-methylimidazolium thiocyanate in acid media follows the Langmuir´s adsorption isotherm. Simulation of interactions between 1- ethyl 3-methylimidazolium thiocyanate and SO4 2− and Cl- on Fe and Fe2 O3 (110) plane surfaces confirms a better adsorption behavior in H2 SO4 . Abstract: The corrosion inhibition behavior of 1-ethyl 3-methylimidazolium thiocyanate, (EMIM) + (SCN) − ionic liquid (IL), on API 5 L X52 steel immersed in 0.5 M H2 SO4 and 0.5 M HCl aqueous solutions were studied. The kinetic corrosion parameters were determined using a gravimetrical method and electrochemical tests (polarization curves, electrochemical impedance spectroscopy). The (EMIM) + (SCN) − exhibited good inhibition efficiency, IE, (82.9% and 77.4% for H2 SO4 (75 ppm) and HCl (100 ppm) solutions) properties in both solutions acting as a mixed-type inhibitor. In H2 SO4 the IE increased with increasing IL concentration and temperature, while in HCl IE decreased with the temperature increase. The IL adsorption mechanism followed the Langmuir isotherm, presenting a competition between the physical and chemical interactions. Surface analysis techniques (energy dispersive spectroscopy and X-ray photoelectron spectroscopy) indicate that the inhibitor formed a protective film on the steel surface, evidencing the adsorption of the cation (EMIM) + and the anion (SCN) − of the IL on the steel surface, which corroborates that both the (EMIM) + and the (SCN) − of IL interact with the substrate. The evaluation of interactions of (EMIM) + (SCN) − molecules with H2 SO4 and HCl in the presence of water on different surfaces of iron Fe and Fe2 O3 (110) plane was performed, using molecular dynamics to determine the inhibitor adsorption energies in both acid media. The simulation results are in close agreement with the experimental observations that the inhibition efficiency is better in H2 SO4 solution in comparison with that in HCl due to the higher adsorption energy values obtained in H2 SO4 medium.